INFLUENCE OF MOTHER’S DIABETES TYPE I ON PARTICULARITIES OF HEPATOCYTES APOPTOSIS IN FETUSES - Sorokina, I.V.; Protsenko, E.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Morphological particularities of hepatocytes apoptosis in fetuses from mothers with diabetes type I were investigatedon the basis of data of Kharkiv perinatal center and Sumy children pathologoanatomic department.As a result of performed study it was discovered that grade of fetal liver apoptosis depends on severity of mother’s diabetes I.Apoptosis index is reliably higher in liver of fetuses from mothers with I type diabetes comparing to fetuses from healthy mothers. Strong negative correlation has been established between grade of apoptosis and glycogen loss in hepatocytes’ cytoplasm. Thereforemain task for endocrinologists and obstetricians must be the supply of stable compensation of carbohydrates exchange on all fetal development stages – from conception to birth.